(untitled) (American Journal of Islam and Society, 2023)
This article strives to chart the intellectual history of Muslims and the trans-civilizational, discursive tradition of Islam spanning fourteen centuries. It chronicles the scholarly projects shaping Islamic thought as they developed in the wake of the Prophet’s (s) death and intensified in the ensuing centuries despite the numerous changes and tumultuous times the Muslim ummah encountered. Together with an accompanying map and visual timeline, it endeavors to empower students of Islam in general and Islamic Studies programs in particular with an appreciation of the breadth and depth of Muslim intellectual history. The article begins by tracing the foundation of early regional centers, the side-by-side formation of disciplines, the development of the various legal schools as well as the many strains of Islamic thought, and how they not only influenced one another but also became absorbed into mainstream Islam, ending with an overview of the impact of modernity on Islamic thought. Through this effort, I hope that students will be able to cultivate a rudimentary understanding of Islamic scholarship in its historical context, make interdisciplinary connections, critically engage with the individual disciplines in their focused study, and gain an overall nuanced reverence for the collective Muslim intellectual legacy across 1400 years along with the diversified scholarly struggles to diligently honor and observe the message received from the Prophet Muhammad (s). The map and timeline accompanying the present survey of Muslim intellectual history are available here. UPDATE: The author has further collaborated with Muslim Views, a South African newspaper, on African Muslim Intellectual History, which has resulted in an infographic with an addendum of 30 scholars.